GM‐CSF signalling blockade and chemotherapeutic agents act in concert to inhibit the function of myeloid‐derived suppressor cells in vitro. Issue 12 (23rd December 2016) - Gargett, Tessa; Christo, Susan N; Hercus, Timothy R; Abbas, Nazim; Singhal, Nimit; Lopez, Angel F; Brown, Michael P
Abstract : Immune evasion is a recently defined hallmark of cancer, and immunotherapeutic approaches that stimulate an immune response to tumours are gaining recognition. However tumours may evade the immune response and resist immune‐targeted treatment by promoting an immune‐suppressive environment and stimulating the differentiation or recruitment of immunosuppressive cells. Myeloid‐derived suppressor cells (MDSC) have been identified in a range of cancers and are often associated with tumour progression and poor patient outcomes. Pancreatic cancer in particular supports MDSC differentiation via the secretion of granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), and MDSC are believed to contribute to the profoundly immune‐suppressive microenvironment present in pancreatic tumours. MDSC‐targeted therapies that deplete or inhibit this cell population have been proposed as a way to shift the balance in favour of a tumour‐clearing immune response. In this study, we have modelled MDSC differentiation and function in vitro and this has provided us with the opportunity to test a range of potential MDSC‐targeted therapies to identify candidates for further investigation. Using in vitro modelling we show here that the combination of GM‐CSF‐signalling blockade and gemcitabine suppresses both the MDSC phenotype and the inhibition of T‐cell function by MDSC. Cancer: Combining different forms of therapy: Combining immunotherapy and chemotherapy may be the key to improved cancer treatments. Immune suppression is a recognized mechanism whereby tumour cells escape immune detection. The effectiveness of immune‐stimulating therapies when combined with established chemotherapies is unknown. Tessa Gargett from the University of South Australia and her colleagues used a patient‐derived cell culture model to test new immunotherapy candidates for combination with current chemotherapy drugs. They trialed immunotherapies targeted to a tumor‐secreted chemical that promotes myeloid‐derived suppressor cells (MDSCs), immune cells derived from bone marrow that can mediate immune suppression. Combining these agents with the chemotherapy drug gemcitabine suppressed MDSC subtypes, thereby reversing the suppression of those immune cells required for targeted killing of tumour cells. This study is an important step in developing combination immuno‐ and chemotherapies for cancer.